Korean ctenostome bryozoans—observations on living colonies, new records, five new species, and an updated checklist - Seo, Ji-Eun; Chae, Hyun Sook; Winston, Judith E.; Zágoršek, Kamil; Gordon, Dennis P. (Zootaxa, 2018)
This paper describes 12 species of ctenostomes from the marine waters of the Korean Peninsula, including five new species—Alcyonidium bullitum n. sp., Alcyonidium pulposum n. sp., Alcyonidium busanensis n. sp., Immergentia cheongpodensis n. sp. and Penetrantia taeanata n. sp., the latter two constituting shell-borers that ramify within dead mollusk shells. Three previously described species are also newly added to the Korean fauna—Amathia acervata Lamouroux, 1824, Amathia medullaris Mawatari, 1972 and Walkeria prorepens Kubanin, 1992. The nomenclature of known species is updated and a revised checklist of all Korean Ctenostomata is included. New biological information is provided based on observation and microphotography of living and preserved colonies, SEM images of dry material and resin casts of ctenostome borings in mollusk shells.